Dementia: good living in our churches. Issue 3 (14th September 2015) - Farr, Emma-Dawn; Bute, Jennifer
Abstract : Purpose: – The purpose of this paper, "Dementia – good living in our churches" co-authored with Dr Bute who is a retired GP living with dementia, is to encourage the Church of England to do more for people with dementia living within their parishes. Design/methodology/approach: – This document was put together using a case study and a literature review. Findings: – As the age range of the country increases there are an increased number of people attending churches who have diagnosed (or undiagnosed) dementia. This document has found that there are a number of areas that the Church of England needs to work on to help people become enveloped within the churches that many of them knew and have grown up with. Originality/value: – New case study and up to date research.